Penatalaksaan Hiperbillirubin pada Bayi Ny. S dengan Ibu HBSAG Positif di Puskesmas Tuntang - Martiningsih; Vistra Veftisia (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2025)
Icterus or jaundice is a clinical symptom often found in neonates and infants. The condition might arise from physiological or pathological causes. Jaundice is a clinical manifestation signifying an elevated blood level of bilirubin (hyperbilirubinemia). Excessive increase in bilirubin is potentially toxic and might even lead to death. A good and directed clinical approach is very important to evaluate the need for further medical intervention. The purpose of this care is to provide midwifery care to Mrs. S with a positive HbSag mother, with a focus on the management of neonatal jaundice. The research instrument uses a descriptive approach method and is documented in the form of SOAP. In this care, the author collects data through interviews, observations, physical examinations, supporting examinations, documentation studies and bibliographic studies. This research was conducted in July 2025 – October 2025. From the results of the Neonatal visit carried out, the results of the examination from the mother's subjective data said that the baby was born by C-section because the mother was resti, had been given Hb0 immunization and Hyperheb Immunization at the Hospital, currently the baby is lazy to drink, sucking is not strong, from the physical examination it was found that the skin color of the face, neck, chest, and extremities was yellow, from the results of the care given, namely education about danger signs in babies, support the mother to always only give breast milk to her baby, advise the mother to immediately check if there are danger signs that arise. On Telemedecine on September 15, 2025 with the doctor Pediatrician at A Hospital, Mrs. S was advised to be hospitalized for further treatment of jaundice (phototherapy).Based on the results of the comprehensive care report for Mrs. S at the Tuntang Community Health Center, the researcher concluded that jaundice can be prevented by providing breast milk as often as possible and by performing phototherapy, jaundice is reduced, the baby becomes active, and suckles more strongly.     Abstrak Ikterus atau jaundice sering dijumpai pada neonatus dan bayi. Ikterus dapat bersifat fisiologis atau patologis. Pada dasarnya, ikterus merupakan manifestasi klinis peningkatan kadar bilirubin dalam darah atau hiperbilirubinemia. Peningkatan bilirubin yang berlebihan berpotensi toksik dan dapat menyebabkan kematian. Pendekatan klinis yang baik dan terarah sangat penting untuk menentukan secara cepat dan tepat perlunya evaluasi dan intervensi medis lanjutan, Tujuan Asuhan ini untuk memberikan asuhan kebidanan pada By Ny S dengan ibu HbSag positif, dengan fokus pada penatalaksanaan Ikterik neonaturum, Intsrumen penelitian menggunakan metode pendekatan yang bersifat deskriptif dan didokumentasikan dalam bentuk SOAP. Dalam asuhan ini, penulis mengumpulkan data melalui wawancara, observasi, pemeriksaan fisik, pemeriksaan penunjang, studi dokumentasi dan studi daftar pusataka. Penelitian ini dilakukan pada bulan Juli 2025 – Oktober 2025. Dari hasil kunjungan Neonatal yang di lakukan ,di dapat hasil pemeriksaan dari data Subyektif ibu mengatakan bayi lahir secara SC karena ibu resti  ,sudah di berikan imunisasi Hb0 dan Imunisasi Hiperheb di Rs, saat ini bayi malas minum, menghisap kurang kuat, dari pemeriksaan fisik di dapatkan warna kulit muka,leher,dada,dan ektremitas kuning, dari hasil pemberian asuhan yang di berikan yaitu edukasi tentang tanda bahaya pada bayi, suport ibu untuk selalu memberikan Asi saja kepada bayinya, anjurkan ibu untuk segera kontrol bila ada tanda bahaya yang timbul. Pada Telemedecine tanngal 15 September 2025 dengan dokter spesialis Anak Rs A , Bayi ny S di sarankan rawat inap untuk tindakan lanjutan penangganan Ikterik (Fototherapi). Berdasarkan hasil laporan Asuhan Komprehensif pada By ny S di puskesmas Tuntang peneliti memperoleh kesimpulan sebagai berikut ikterik dapat di cegah dengan di berikan Asi sesring mungkin dan di lakukan fototherapi ikterik berkurang ,bayi menjadi aktif,menetek lebih kuat.